CuO@C / AC catalyst, and preparation method and application thereof

CN122875221APending Publication Date: 2026-10-09NANJING TECH UNIV
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611218186.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-08-12
Publication Date
2026-10-09

AI Technical Summary

Technical Problem

[0004]针对上述现有技术对抗生素等有机污染物去除率低的问题,本发明目提供一种制备简单、成本低廉的CuO@C/AC催化剂及其制备方法和应用,该催化剂既具有氧化功能又具有较大的比表面,以及过硫酸盐活化、Cu2+/ Cu+与AC的协同作用,可促进多种活性氧物种生成1O2、•O2−、•OH、SO4−•,并彻底降解氧氟沙星等难降解有机污染物

Benefits of technology

金属有机框架(MOFs)具有高比表面积、可调结构和优异的化学稳定性,但是在水中的稳定性较差。作为一种MOFs材料,Cu-BTC由铜离子和均苯三甲酸作为连接体构成,具有丰富的孔隙度和较大的比表面积,为催化反应提供了有利的微环境,基于Cu-MOF的CuO@C可显著提高催化剂的稳定性。作为载体的高比表面积、多孔结构及丰富表面官能团的活性炭,既能强化污染物吸附,又可作为载体抑制金属纳米颗粒团聚。此外,AC自身具有活化过硫酸盐产生活性氧的能力,也能大幅提高催化效果。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122875221A_ABST
    Figure CN122875221A_ABST
Patent Text Reader

Abstract

This invention provides a CuO@C / AC catalyst, its preparation method, and its application. The catalyst comprises a support and CuO@C particles supported thereon. The support is activated carbon, and the CuO@C particles are obtained by in-situ calcination of Cu-MOFs. This CuO@C / AC catalyst exhibits excellent degradation performance in the oxidation and degradation of organic pollutants using sodium persulfate, achieving a 97.19% removal rate of ofloxacin in 30 minutes. After 10 cycles, the removal rate of ofloxacin remains above 96.8%. Free radical quenching experiments show that the high efficiency of ofloxacin degradation is mainly attributed to sodium persulfate and... 1 O2、•O 2− •OH and SO4 − • Synergistic effect of active species. The catalyst of this invention has the advantages of being economical and environmentally friendly, simple to operate, low in cost, and highly efficient in degradation, and has certain industrial application value.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of green catalysis and environmental chemistry, specifically relating to a CuO@C / AC catalyst, its preparation method, and its application in the degradation of wastewater containing organic pollutants. Background Technology

[0002] Antibiotics, as antibacterial drugs, have played a vital role in the history of human societal development. Hundreds of thousands of tons of antibiotics are used annually in clinical medicine and aquaculture. However, in actual production, wastewater from the pharmaceutical industry, medical institutions, and aquaculture often contains high concentrations of antibiotic residues. These antibiotics and their metabolites remaining in water bodies inevitably disrupt the original ecological balance of the aquatic environment, and the accumulation of antibiotics poses a serious threat to human health. Therefore, developing efficient and sustainable treatment technologies is crucial for solving antibiotic pollution in wastewater.

[0003] Advanced oxidation processes (AOPs), by generating highly reactive free radicals, have been extensively studied for the degradation of recalcitrant organic pollutants. Traditional AOPs, such as the Feton process and ozone systems, have several limitations, including a narrow operating pH range and Cu... 2+ / Cu + The redox cycle is slow, the system is unstable, and there are potential toxicity issues. Photocatalysis is limited by low carrier utilization and rapid electron-hole recombination. Electrochemical advanced oxidation processes have shown great potential for pollutant removal. However, their application is still limited by high electrode costs, high energy consumption, and pH sensitivity. Summary of the Invention

[0004] To address the low removal rate of organic pollutants such as antibiotics in existing technologies, this invention provides a simple and low-cost CuO@C / AC catalyst, its preparation method, and its applications. This catalyst possesses both oxidation capabilities and a large specific surface area, and is activated by persulfate and Cu. 2+ / Cu + Synergistic effects with AC can promote the generation of various reactive oxygen species. 1 O2、•O 2− •OH, SO4 − • It can completely degrade recalcitrant organic pollutants such as ofloxacin. This catalyst is simple to prepare, inexpensive, and environmentally friendly, providing a novel catalyst for persulfate activation in water treatment.

[0005] To achieve the above objectives, the present invention adopts the following technical solution: A CuO@C / AC catalyst includes a support and CuO@C particles supported thereon, wherein the support is activated carbon and the CuO@C particles are obtained by in-situ calcination of Cu-MOFs.

[0006] Preferably, the Cu-MOFs are Cu-BTC.

[0007] Preferably, the Cu-MOFs are formed in situ on the surface of the activated carbon.

[0008] Preferably, the mass ratio of Cu to activated carbon in the catalyst is 1:(5~12); most preferably, it is 1:(7~11).

[0009] A second objective of this invention is to provide a method for preparing the above-mentioned catalyst, comprising the following steps: (1) Immerse activated carbon (AC) in a copper salt solution, and after adsorption, add a solution of trimesic acid (BTC) to it, followed by ultrasonic treatment; (2) The solution obtained in step (1) is subjected to a solvothermal reaction to obtain Cu-BTC / AC; (3) Calcine Cu-BTC / AC in a protective atmosphere to obtain the product.

[0010] Preferably, the molar ratio of Cu element and pyromellitic acid in the copper salt in step (1) is 3~1:1, preferably 1.65:1.

[0011] Preferably, the copper salt in step (1) is copper acetate.

[0012] Preferably, the solvent for the copper salt solution in step (1) is an ethanol-water solvent, and more preferably, the volume ratio of ethanol to water is 1:1.

[0013] Preferably, the activated carbon in step (1) is in powder form.

[0014] Preferably, the solvent of the pyromellitic acid solution in step (1) is methanol-DMF solvent, and more preferably, the volume ratio of methanol to DMF is 1:1.

[0015] Preferably, the temperature of the solvothermal reaction in step (2) is 100℃~160℃, and the reaction time is 12~24h. More preferably, the temperature of the solvothermal reaction is 120℃, and the reaction time is 20h.

[0016] Preferably, step (2) further includes washing, filtering and drying the product after the heat of solution reaction.

[0017] Preferably, the calcination temperature in step (3) is 350~600℃, and the calcination time is 1~4 h. More preferably, the calcination temperature is 450℃, and the calcination time is 2 h.

[0018] Preferably, the protective atmosphere described in step (3) is an N2 atmosphere.

[0019] Preferably, the heating rate of calcination in step (3) is 5°C / min.

[0020] Preferably, the activated carbon is coconut shell charcoal, chestnut shell charcoal, peanut shell charcoal, molasses charcoal, straw charcoal, cellulose charcoal, or starch charcoal.

[0021] A third objective of this invention is to provide the application of the above-mentioned CuO@C / AC catalyst in the oxidative degradation of organic pollutants in wastewater.

[0022] The application includes: in the presence of the catalyst, contacting wastewater containing organic pollutants with an oxidant to carry out an oxidative degradation reaction.

[0023] Preferably, the organic pollutant is one or more of ofloxacin, ciprofloxacin, norfloxacin, moxifloxacin, enrofloxacin, or methylene blue.

[0024] Preferably, the oxidant is sodium persulfate (sodium persulfate monosulfate or sodium persulfate disulfate), and more preferably, the oxidant is sodium persulfate disulfate.

[0025] Preferably, the concentration of the oxidant is 0.1~0.5 g / L, more preferably 0.30 g / L.

[0026] Preferably, the amount of CuO@C / AC catalyst used is 0.1~0.4 g / L, more preferably 0.25 g / L.

[0027] Preferably, the oxidative degradation reaction takes 5 to 60 minutes, more preferably 30 minutes.

[0028] The oxidative degradation reaction is carried out under stirring conditions. Preferably, the stirring speed is 300~800 r / min, wherein the optimal stirring speed is 500 r / min.

[0029] The beneficial effects of this invention are as follows: Metal-organic frameworks (MOFs) possess high specific surface area, tunable structure, and excellent chemical stability, but their stability in water is poor. Cu-BTC, as a MOF material, is composed of copper ions and trimesic acid as linkers, exhibiting abundant porosity and a large specific surface area, providing a favorable microenvironment for catalytic reactions. CuO@C based on Cu-MOF can significantly improve catalyst stability. Activated carbon, with its high specific surface area, porous structure, and abundant surface functional groups, can both enhance pollutant adsorption and inhibit the aggregation of metal nanoparticles. Furthermore, activated carbon itself has the ability to activate persulfate to generate reactive oxygen species, which can also significantly improve catalytic performance.

[0030] The CuO@C / AC catalyst prepared in this invention is a composite material composed of MOF-derived copper oxide and bio-activated carbon. The active component of the catalyst in this invention is Cu. 2+ The active component grows on the nodes of the MOF, and the active component will not be lost due to shedding or leaching. Moreover, the catalyst can be recovered, which greatly saves raw material costs.

[0031] The preparation process of the CuO@C / AC catalyst of the present invention is simple, and the catalyst has high atom economy.

[0032] The CuO@C / AC catalyst of the present invention is easy to recover after the oxidative degradation reaction of organic pollutants such as oxyfluoroquinolone in wastewater is completed, and the catalyst has good stability. Attached Figure Description

[0033] Figure 1 The image shows the XRD pattern of Cu@C / 10AC prepared in the example.

[0034] Figure 2 This is a diagram showing the adsorption / desorption and pore size distribution of Cu@C / 10AC prepared in Example 1.

[0035] Figure 3 This is a SEM image of Cu@C / 10AC prepared in Example 1. Detailed Implementation

[0036] The present invention will now be described in more detail with reference to the embodiments, which do not limit the scope of protection of the present invention.

[0037] Example 1 1.0507 g (5 mmol) of BTC was dissolved in 20 mL of methanol / DMF (volume ratio 1:1) mixed solvent and stirred for 30 min to obtain solution A. 1.646 g of Cu(CH3COO)2·H2O was dissolved in 25 mL of ethanol / H2O (volume ratio 1:1) mixed solvent and stirred for 30 min to obtain solution B. 5.24 g of AC powder was slowly added to solution B to obtain solution C. Solution A was then slowly added to solution C. The mixture was sonicated at room temperature for 30 min and then transferred to an autoclave and reacted at 120 °C for 20 h. The resulting mixture was the Cu-BTC / 10AC. Finally, the solid Cu-BTC / AC powder was placed in a tube furnace and heated to 450 °C at a heating rate of 5 °C / min under N2 protection and held for 2 h. After natural cooling to room temperature, a black Cu@C / 10AC composite catalyst was obtained.

[0038] The XRD pattern of the prepared Cu@C / 10AC was obtained by Figure 1 As shown.

[0039] The adsorption-desorption and pore size distribution of the prepared Cu@C / 10AC were obtained from... Figure 2 As shown.

[0040] The SEM image of the prepared Cu@C / 10AC is shown below. Figure 3 As shown.

[0041] Depend on Figure 1 It can be seen that a very sharp and high-intensity diffraction peak appears near 35.5° in the XRD pattern of Cu@C / 10AC. This is the most typical characteristic peak of CuO, indicating that there is a well-crystallized CuO phase in the catalyst.

[0042] Depend on Figure 2 It can be seen that the CuO@C / AC catalyst exhibits a type IV isotherm and an H3 type hysteresis loop, indicating that it retains the mesoporous structure characteristics of the activated carbon support, with layered particles agglomerating to form fissure-like pores.

[0043] from Figure 3 As can be seen, (a) shows that CuO nanoparticles are uniformly dispersed on the surface of activated carbon, and (b) confirms that the activated carbon maintains an irregular blocky porous morphology, and the carbon coating layer effectively coats the active components.

[0044] Catalyst performance evaluation: The catalyst Cu@C / 10AC was used at a dosage of 0.25 g / L. 200 mL of a 30 mg / L ofloxacin solution was added to the reaction vessel, along with 0.30 g / L sodium persulfate. The reaction was stirred at room temperature for 30 min. After the reaction, the degradation rate of ofloxacin was measured to be 97.19%. After 10 cycles of use, the removal rate of ofloxacin remained above 96.8%, with no significant decrease in catalyst activity or ofloxacin degradation rate. Under the same conditions, catalyst Cu@C / 10AC-4 degraded ciprofloxacin, norfloxacin, moxifloxacin, enrofloxacin, and methylene blue, with degradation rates of 97.71%, 90.48%, 93.94%, 95.23%, and 99.92%, respectively. These data indicate that catalyst Cu@C / 10AC-4 has potential application value in degrading pollutants.

[0045] Example 2 The preparation of Cu@C / 10AC1 is the same as in Example 1, except that the calcination temperature of Cu-BTC / 10AC is 500℃.

[0046] Solid powder Cu-BTC / 10AC was placed in a tube furnace and heated to 500℃ at a heating rate of 5℃ / min under N2 protection, and held at that temperature for 2 h; it was then naturally cooled to room temperature to obtain a black Cu@C / 10AC1 composite catalyst.

[0047] The performance evaluation of the catalyst was the same as in Example 1, except that the catalyst Cu@C / 10AC1 prepared in Example 2 showed a degradation rate of 95.38% for ofloxacin after 30 min of degradation at room temperature. After 10 cycles of use, the removal rate of ofloxacin remained above 94.6%, and there was no significant decrease in catalyst activity or ofloxacin degradation rate.

[0048] Example 3 The molar ratio of Cu to 1,3,5-tristyrene (BTC) is 1:1, and the mass ratio of Cu to activated carbon is 1:7.

[0049] 1.7325 g (8.2 mmol) of BTC was dissolved in 20 mL of methanol / DMF (volume ratio 1:1) mixed solvent and stirred for 30 min to obtain solution A. 1.646 g of Cu(CH3COO)2·H2O was dissolved in 25 mL of ethanol / H2O (volume ratio 1:1) mixed solvent and stirred for 30 min to obtain solution B. 3.668 g of AC powder was slowly added to solution B to obtain solution C. Solution A was then slowly added to solution C. The mixture was sonicated at room temperature for 30 min and then transferred to an autoclave and reacted at 160 °C for 12 h. The resulting mixture was the Cu-BTC / 7AC. Finally, the solid Cu-BTC / AC powder was placed in a tube furnace and heated to 350 °C at a heating rate of 5 °C / min under N2 protection and held for 4 h. After natural cooling to room temperature, a black Cu@C / 7AC composite catalyst was obtained.

[0050] The catalyst performance evaluation was the same as in Example 1. The catalyst CuO@C / 7AC prepared in Example 3 showed a degradation rate of 92.5% for ofloxacin after 30 min of degradation at room temperature. After 10 cycles of use, the removal rate of ofloxacin remained above 91.8%, and there was no significant decrease in catalyst activity or ofloxacin degradation rate.

[0051] Example 4 The molar ratio of Cu to 1,3,5-tristyrene (BTC) was 3:1, and the mass ratio of Cu to activated carbon was 1:12.

[0052] 0.5775 g (2.75 mmol) of BTC was dissolved in 20 mL of methanol / DMF (volume ratio 1:1) and stirred for 30 min to obtain solution A. 1.646 g of Cu(CH3COO)2·H2O was dissolved in 25 mL of ethanol / H2O (volume ratio 1:1) and stirred for 30 min to obtain solution B. 6.29 g of AC powder was slowly added to solution B to obtain solution C. Solution A was then slowly added to solution C. The mixture was sonicated at room temperature for 30 min and then transferred to an autoclave and reacted at 100 °C for 24 h. The resulting mixture was the Cu-BTC / 12AC. Finally, the solid Cu-BTC / AC powder was placed in a tube furnace and heated to 600 °C at a heating rate of 5 °C / min under N2 protection, and held for 1 h. After natural cooling to room temperature, a black Cu@C / 12AC composite catalyst was obtained.

[0053] The catalyst performance evaluation was the same as in Example 1. The catalyst CuO@C / 12AC prepared in Example 4 showed a degradation rate of 96.14% for ofloxacin after 30 min of degradation at room temperature. After 10 cycles of use, the removal rate of ofloxacin remained above 95.24%, and there was no significant decrease in catalyst activity or ofloxacin degradation rate.

[0054] Example 5 The preparation of Cu@C / 10AC-2 was the same as in Example 1, except that the solid powder Cu-BTC / AC was placed in a tube furnace and heated to 400°C at a heating rate of 5°C / min under N2 protection, and held for 2 h; it was then naturally cooled to room temperature to obtain the black Cu@C / 10AC-2 composite catalyst.

[0055] The catalyst performance evaluation was the same as in Example 1. The catalyst Cu@C / 10AC-2 prepared in Example 6 showed a degradation rate of 96.8% for ofloxacin after 30 min of degradation at room temperature. After 10 cycles of use, the removal rate of ofloxacin remained above 95.24%, and there was no significant decrease in catalyst activity or ofloxacin degradation rate.

[0056] Example 6 The preparation of Cu@C / 10AC-3 was the same as in Example 1, except that the solid powder Cu-BTC / AC was placed in a tube furnace and heated to 550°C at a heating rate of 5°C / min under N2 protection, and held for 2 h; it was then naturally cooled to room temperature to obtain the black Cu@C / 10AC-3 composite catalyst.

[0057] The catalyst performance evaluation was the same as in Example 1. The catalyst Cu@C / 10AC-3 prepared in Example 7 showed a degradation rate of 94.6% for ofloxacin after degradation at room temperature for 30 min. After 10 cycles of use, the removal rate of ofloxacin remained above 92.83%, and there was no significant decrease in catalyst activity or ofloxacin degradation rate.

[0058] Comparative Example 1 Preparation of Cu@C / 10AC-4 catalyst based on Cu-BTC synthesized in situ: 1.0507 g (5 mmol) of BTC was dissolved in 20 mL of a methanol / DMF (1:1 volume ratio) mixed solvent and stirred for 30 min to obtain solution A. 1.646 g of Cu(CH3COO)2·H2O was dissolved in 25 mL of an ethanol / H2O (1:1 volume ratio) mixed solvent and stirred for 30 min to obtain solution B. Solution A was dissolved in solution B, and the resulting mixture was sonicated at room temperature for 30 min and then transferred to an autoclave and reacted at 120 °C for 20 h. The resulting mixture was the Cu-BTC. Finally, the solid Cu-BTC powder was placed in a tube furnace and heated to 450 °C at a heating rate of 5 °C / min under N2 protection and held for 2 h. After natural cooling to room temperature, a black Cu@C composite catalyst was obtained.

[0059] 5.24 g of AC powder was slowly added to an aqueous solution of Cu@C, mixed and stirred for 4 h, centrifuged, filtered, and dried to obtain Cu@C / 10AC-4.

[0060] The catalyst performance evaluation was the same as in Example 1. The catalyst Cu@C / 10AC-4 prepared in Example 5 showed a degradation rate of 82.7% for ofloxacin after 30 min of degradation at room temperature. After 10 cycles of use, the removal rate of ofloxacin remained above 76.35%, although the catalyst activity and the degradation rate of ofloxacin decreased slightly.

[0061] Comparative Example 2 Cu-BTC and CuO@C were prepared using the same method as in Comparative Example 1.

[0062] 1.0507 g (5 mmol) of BTC was dissolved in 20 mL of a methanol / DMF (1:1 volume ratio) mixed solvent and stirred for 30 min to obtain solution A. 1.646 g of Cu(CH3COO)2·H2O was dissolved in 25 mL of an ethanol / H2O (1:1 volume ratio) mixed solvent and stirred for 30 min to obtain solution B. Solution A was slowly added to solution B, and the mixture was sonicated at room temperature for 30 min, then transferred to an autoclave and reacted at 120 °C for 20 h. The resulting mixture is the solid powder Cu-BTC.

[0063] Solid Cu-BTC powder was placed in a tube furnace and heated to 450°C at a heating rate of 5°C / min under N2 protection, and held at that temperature for 2 h; it was then naturally cooled to room temperature to obtain a black Cu@C catalyst.

[0064] 1.646 g of Cu(CH3COO)2·H2O was dissolved in 25 mL of ethanol / H2O (volume ratio 1:1) and stirred for 30 min to obtain solution A. 5.24 g of AC powder was slowly added to solution A. The mixture was sonicated at room temperature for 30 min and then dried in an oven at 120 °C for 20 h to obtain a black solid powder Cu / AC. The solid powder Cu / AC was placed in a tube furnace and heated to 450 °C at a heating rate of 5 °C / min under N2 protection, and held at that temperature for 2 h. After naturally cooling to room temperature, a black CuO / AC catalyst was obtained.

[0065] Catalyst performance evaluation: The dosage of catalysts Cu-BTC, CuO@C, and CuO / AC was 0.25 g / L. 200 mL of a 30 mg / L ofloxacin solution was added to the reaction vessel, followed by 0.30 g / L sodium persulfate. The reaction was stirred at room temperature for 30 min. The degradation rate of ofloxacin after the reaction was completed is shown in Table 1. .

[0066] As shown in Table 1, the degradation rates of ofloxacin using a single Cu-BTC precursor or simple carbon-coated CuO (CuO@C) were only 26.19% and 10.37%, respectively, due to the lack of effective pore support. While CuO / AC directly supported on activated carbon increased the degradation rate to 87.75% by leveraging the pore advantages of AC, the stability of the active component was insufficient. This invention, through a synergistic design strategy of carbon coating followed by support loading, prepares a CuO@C / AC catalyst that fully utilizes the activity regulation and protection effects of the carbon coating layer, as well as the adsorption, enrichment, and mass transfer advantages of the activated carbon support, achieving a ofloxacin degradation rate of 99%, significantly superior to existing single-structure catalysts. This provides a highly efficient and stable catalytic material for antibiotic wastewater treatment.

[0067] It is recommended to supplement comparative examples of MOFs formed by different Cu ligands to demonstrate that Cu-BTC in this invention is the most effective catalyst precursor. It is also recommended to supplement this with a simple mechanistic description, i.e., what structural characteristics of Cu-BTC lead to the best catalytic effect of CuO calcined from it as a precursor. Comparative Example 3 0.417 g (3 mmol) of pyridine-2,6-diethanol was dissolved in 5 mL of methanol and stirred to obtain solution A. 0.362 g (1.5 mmol) of Cu(NO3)2·3H2O was dissolved in a small amount of methanol and stirred until completely dissolved to obtain solution B. Solution B was slowly added to solution A, and the mixture changed from colorless to blue. Stirring continued for 10 min. 0.468 g (3 mmol) of 4,4'-bipyridine was dissolved in 5 mL of methanol to obtain solution C. Solution C was added dropwise to the above blue mixture, and stirring continued at room temperature for 30 min to ensure thorough mixing of the ligands. The resulting mixture was transferred to a beaker, covered with sealing film and punctured, and placed in a fume hood for slow evaporation at room temperature. After about one week, blue blocky crystals precipitated at the bottom of the beaker. The collected crystals were Cu-MOF.

[0068] Solid Cu-MOF powder was placed in a tube furnace and heated to 450°C at a heating rate of 5°C / min under N2 protection, and held for 2 h; it was then naturally cooled to room temperature to obtain a black mCuO@C catalyst.

[0069] 0.417 g (3 mmol) of pyridine-2,6-diethanol was dissolved in 5 mL of methanol and stirred to obtain solution A. 0.362 g (1.5 mmol) of Cu(NO3)2·3H2O was dissolved in a small amount of methanol and stirred until completely dissolved to obtain solution B. Solution B was slowly added to solution A; the mixture changed from colorless to blue. Stirring continued for 10 min to obtain solution C. 0.95 g of activated carbon was added to solution C and stirred for 10 min. 0.468 g (3 mmol) of 4,4'-bipyridine was dissolved in 5 mL of methanol to obtain solution D. Solution D was added dropwise to the above mixture, and stirring continued at room temperature for 30 min to ensure thorough mixing of the ligands. The resulting mixture was transferred to a beaker, covered with sealing film and punctured, and placed in a fume hood for slow evaporation at room temperature. After approximately one week, crystals precipitated at the bottom of the beaker, which is Cu-MOF / AC.

[0070] Solid Cu-MOF / AC powder was placed in a tube furnace and heated to 450℃ at a heating rate of 5℃ / min under N2 protection, and held at that temperature for 2 h; it was then naturally cooled to room temperature to obtain a black mCu@C / 10AC catalyst.

[0071] Catalyst performance evaluation: The dosage of catalysts Cu-MOF, mCuO@C, and mCu@C / 10AC was 0.25 g / L. 200 mL of 30 mg / L ofloxacin solution was added to the reaction vessel, and 0.30 g / L sodium persulfate was added. After stirring at room temperature for 30 min, the degradation rate of ofloxacin was measured and shown in Table 2.

[0072] .

[0073] As shown in Table 2, the degradation rates of ofloxacin by the Cu-MOF-1 precursor constructed with pyridine-2,6-dimethylethanol and 4,4'-bipyridine as ligands and its derivative materials mCuO@C and mCu@C / 10AC were only 11.33%, 5.79% and 36.85%, respectively, which were significantly lower than those of the Cu-BTC system constructed with pyromellitic acid as ligand in this invention (Cu-BTC was 26.19%, CuO@C was 10.37%, and CuO / AC was 87.75%). The reason for this is that Cu-MOF-1 lacks a three-dimensional "pore cage-channel" structure and abundant open copper metal sites similar to Cu-BTC. The carbon-coated material obtained after its pyrolysis is difficult to form an effective active interface and mass transfer channel. Even with the aid of activated carbon support, the degradation rate improvement is limited due to the insufficient dispersion and thermal stability of the copper species in the precursor itself, far less effective than CuO / AC in this invention, and even less comparable to CuO@C / AC (99% degradation rate) designed with prior carbon coating followed by support loading. The above comparison further confirms that the ligand structure of the MOF precursor has a decisive influence on the final catalytic performance. The Cu-BTC selected in this invention, with its unique skeletal advantages, provides the optimal structural basis for persulfate activation and efficient ofloxacin degradation.

[0074] Comparative Example 4 5.46 g (18 mmol) of Co(NO3)2·6H2O was weighed and dissolved in 75 mL of methanol, and stirred until completely dissolved to obtain solution A. 6.16 g (75 mmol) of 2-methylimidazole was weighed and dissolved in 75 mL of methanol, and stirred until completely dissolved to obtain solution B. Solution A was slowly poured into solution B, and the mixture was stirred at room temperature for 6 h. After the reaction was complete, the resulting purple precipitate was filtered, washed three times with methanol, and dried overnight in an oven at 80 °C to obtain a purple Co-ZIF-67 solid powder.

[0075] Solid powder Co-ZIF-67 was placed in a tube furnace and heated to 450°C at a heating rate of 5°C / min under N2 protection, and held at that temperature for 2 h; it was then naturally cooled to room temperature to obtain a black CoO@C catalyst.

[0076] 5.46 g (18 mmol) of Co(NO3)2·6H2O was weighed and dissolved in 75 mL of methanol, and stirred until completely dissolved to obtain solution A. 6.16 g (75 mmol) of 2-methylimidazole was weighed and dissolved in 75 mL of methanol, and stirred until completely dissolved to obtain solution B. 11.06 g of activated carbon was weighed and added to solution B, and stirred for 10 min. Solution A was slowly poured into the mixed solution, and the mixture was stirred at room temperature for 6 h. After the reaction was complete, the resulting purple precipitate was filtered, washed three times with methanol, and dried overnight in an oven at 80 °C to obtain Co-ZIF-67 / AC solid powder.

[0077] Solid powder Co-ZIF-67 / AC was placed in a tube furnace and heated to 450℃ at a heating rate of 5℃ / min under N2 protection, and held at that temperature for 2 h; it was then naturally cooled to room temperature to obtain a black Co@C / 10AC catalyst.

[0078] Catalyst performance evaluation: The dosage of catalysts Co-ZIF-67, CoO@C, and Co@C / 10AC was 0.25 g / L. 200 mL of 30 mg / L ofloxacin solution was added to the reaction vessel, and 0.30 g / L sodium persulfate was added. After stirring at room temperature for 30 min, the degradation rate of ofloxacin was measured and shown in Table 3.

[0079] .

[0080] As shown in Table 3, the degradation rate of the single Co-ZIF-67 precursor was only 14.21% due to its limited adsorption and activation capacity for ofloxacin caused by its microporous structure. Although the carbon-coated CoO@C achieved carbon encapsulation of cobalt species to a certain extent, the excessively thick carbon layer hindered the exposure of active sites, resulting in a decrease in the degradation rate to 5.82%. While the Co@C / 10AC obtained by directly loading CoO@C onto activated carbon increased the degradation rate to 24.78% by leveraging the pore adsorption and enrichment effect of activated carbon, the cobalt species were prone to agglomeration during the pyrolysis of the precursor, and the interfacial synergy between the precursor and the carbon support was weak, resulting in insufficient stability of the active components. The degradation rate was far lower than that of CuO / AC (87.75%) and CuO@C / AC (99%) under the same conditions in the Cu-BTC system of this invention. The above comparison shows that the metal species and ligand structure of the MOF precursor together determine the upper limit of the performance of the derived catalytic material. The Cu-BTC selected in this invention, with its three-dimensional open "pore cage-channel" framework and abundant unsaturated copper sites, is more conducive to forming a synergistic interface between highly dispersed active species and conductive carbon network during pyrolysis, thus exhibiting a significantly better catalytic efficiency than the Co-based system in the persulfate-activated degradation of ofloxacin reaction.

Claims

1. A CuO@C / AC catalyst, characterized in that, It includes a carrier and CuO@C particles loaded thereon, wherein the carrier is activated carbon and the CuO@C particles are obtained by in-situ calcination of Cu-MOFs; preferably, the Cu-MOFs are formed in-situ on the surface of the activated carbon.

2. The catalyst according to claim 1, characterized in that, The Cu-MOFs are Cu-BTC.

3. The catalyst according to claim 1, characterized in that, In the catalyst, the mass ratio of Cu to activated carbon is 1:(5~12); preferably 1:(7~11).

4. The method for preparing the catalyst according to any one of claims 1-3, characterized in that, Includes the following steps: (1) Immerse activated carbon in a copper salt solution, and after adsorption, add a solution of trimesic acid to it, followed by ultrasonic treatment; (2) The solution obtained in step (1) is subjected to a solvothermal reaction to obtain Cu-BTC / AC; (3) Calcine Cu-BTC / AC in a protective atmosphere to obtain the final product.

5. The preparation method according to claim 4, characterized in that, The molar ratio of Cu element and pyromellitic acid in the copper salt described in step (1) is 3~1:1, preferably 1.65:

1.

6. The preparation method according to claim 4, characterized in that, The temperature of the solvothermal reaction in step (2) is 100℃~160℃ and the reaction time is 12~24 h; preferably, the temperature of the solvothermal reaction is 120℃ and the reaction time is 20 h.

7. The preparation method according to claim 4, characterized in that, The calcination temperature in step (3) is 350~600℃ and the calcination time is 1~4 h; preferably, the calcination temperature is 450℃ and the calcination time is 2 h.

8. The application of the catalyst according to any one of claims 1-3 in the oxidative degradation of organic pollutants in wastewater, characterized in that, The application includes: in the presence of the catalyst, contacting wastewater containing organic pollutants with an oxidant to carry out an oxidative degradation reaction.

9. The application according to claim 8, characterized in that, The oxidant is sodium persulfate.

10. The application according to claim 8, characterized in that, The organic pollutant is one or more of ofloxacin, ciprofloxacin, norfloxacin, moxifloxacin, enrofloxacin, or methylene blue.